Diversification of Food Consumption for Food Security Based on Local Potency at Household Level in Semin, Gunung Kidul - Made Suyastiri.YP Ni (Universitas Islam Indonesia, 2008)
The purpose of the research is to investigate and analyze factors influecing consumption diversification system based on local potency to create household food security. This research uses descriptive method from survey result.Research area is determined by purposive method and household sample is taken by proportional stratified random sampling with 50 households. The result of this research indicates that staple food based on local potency is still dominated by rice followed by cassava and corn. Staple food diversification system is rice, and rice substitution like corn, rice-corn, rice-cassava, and rice-corn-cassava. Factors which influence household consumption diversification system is food prices, household income, and number of family memberKeywords: diversification, food security, consumption, staple food